Maternal and foetal outcome in patients of gestational diabetes mellitus - ., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Indian women have high Prevalence of diabetes and their relative risk of developing gestational diabetes mellitus (GDM) is 11.3 times compared to white women. The metabolic adaptations during pregnancy are designed to maintain a continuous availability of substrate to accommodate the fetal growth. Aims of present study were the antenatal screening of Gestational diabetes mellitus and its pregnancy outcome. Methods: The present study is a type of prospective study in this study 6000 pregnant women were randomly selected for screening irrespective of gestational age and any of the risk factor. All consenting pregnant, who came for first absolute neutrophil count in outpatient department, pregnant women of any parity, and singleton pregnancies were included. Results: Out of 6000 women screened 200 were found positive for GDM. The study indicated that GDM was 3.33%. The incidence of GDM was found to be more in women > 25 years age. Fetal outcome was satisfactory in well controlled GDM, only 7 babies were macrosomic, 13 intrauterine death and 5 still birth, 10 babies required NICU admission for hypoglycemia, respiratory distress syndrome, septicemia. Conclusions: Fetal outcome was satisfactory in well controlled GDM. There was no neonatal mortality. Hence, GDM and its complications are preventable.